Effectiveness of educational interventions for improving rabies prevention in children: A systematic review and meta-analysis - Nopphadol Janeaim; Charin Suwanwong; Pitchada Prasittichok; Kanu Priya Mohan; Suchitra Hudrudchai (Journal of Education and Health Promotion)
Rabies poses a significant global health threat, particularly to school-age children through dog bites. This systematic review aimed to investigate the effectiveness of educational interventions for improving rabies prevention among children. In this review, a comprehensive search was conducted across several electronic databases (PubMed, SCOPUS, EBSCO, Google Scholar, and Thai Citation Index) to identify relevant articles published between 2014 and 2023, following PRISMA guidelines. Data on intervention characteristics, outcomes measures, and findings were extracted. The Joanna Briggs Institute appraisal tool was used to assess the quality of the included studies. Of 788 articles, 11 met inclusion criteria. Results demonstrated the efficacy of educational interventions in increasing rabies knowledge, perceived vulnerability to rabies, and rabies preventive behaviors. Additionally, there was evidence suggesting that educational interventions related to rabies and safety information around dogs may be more effective in improving rabies knowledge and perceived vulnerability to rabies among experimental groups compared with control groups. However, this did not significantly improve rabies prevention behaviors. These findings highlighted the imperative for targeted, well-designed educational strategies, collaboratively delivered with educators, to ensure a sustained impact, especially among vulnerable populations such as school-age children.